2008
DOI: 10.1007/s00701-007-1457-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemifacial spasm: neurovascular compressive patterns and surgical significance

Abstract: Once the compressing vessel responsible for the neurovascular compression are identified, the probable pattern of compression can be anticipated; this knowledge could facilitate the application of the appropriate operative procedures and minimise post-operative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 25 publications
1
33
1
1
Order By: Relevance
“…36 As the neurovascular confliction theory has been accepted worldwide as the etiology of the disease, this process should give rise to an immediate pain free once the offending vessel was removed from the trigeminal nerve. 15,16,37,[61][62][63][64][65][66][67][68][69][70][71] Nevertheless, the common cure rate was found to be less than 90% in this research, which implied that this process needs to be further refined.…”
Section: Discussioncontrasting
confidence: 65%
“…36 As the neurovascular confliction theory has been accepted worldwide as the etiology of the disease, this process should give rise to an immediate pain free once the offending vessel was removed from the trigeminal nerve. 15,16,37,[61][62][63][64][65][66][67][68][69][70][71] Nevertheless, the common cure rate was found to be less than 90% in this research, which implied that this process needs to be further refined.…”
Section: Discussioncontrasting
confidence: 65%
“…In the present study, the most frequent offending vessels were PICA and VB, as found in previous reports 4 13 16 26. However, several studies showed multiple sites of nerve compression at the origin of primary HFS 3 13 26.…”
Section: Discussionsupporting
confidence: 89%
“…Mooij et al 25 reported a similar experience of LSR disappearance after drainage of cerebrospinal fluid. In rare cases, the outflow of cerebrospinal fluid may consistently change the anatomical relationship between the facial nerve and a compressive vessel 11 12 19 26…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic variations in vasculature such as lateral deviation of one or both vertebral arteries occurred on the ipsilateral side of HFS in 86.4% cases, making these variations a HFS risk factor [32]. The pattern of neurovascular compression can be divided into six different categories: (A) loop type, where the vascular itself creates the compression, (B) arachnoid type, where arachnoid trabeculae between the vessel and brainstem cause the vessel to tether to the nerve, (C) perforator type, where the perforating arteries from the compressing vessel tether the vessel to the brainstem, (D) branch type, where the nerve is caught between the compressing vessel and its branches, (E) sandwich type, where the nerve is sandwiched between two different vessels, and (F) tandem type, where one vessel compresses another vessel that compresses the nerve [33]. Multiple vessel compressions have been observed in 38% of HFS cases [23].…”
Section: Etiologymentioning
confidence: 99%